Do local governments use municipal companies for off-balance-sheet financing? - Weronika Stobieniecka; Anna Białek-Jaworska (Central European Economic Journal (CEEJ), 2020)
This paper investigates whether municipalities in Poland use their municipal companies to increase debt capacity beyond the limitations imposed by the fiscal debt rules. The article presents corporate governance and agency problems on the example of relations between local government units and affiliated companies. We review and link literature on corporate finance, in particular capital structure, and public finance - debt liabilities of municipalities. We analyse a sample of 2,019 observations of municipalities and their municipal companies using the Ordinary Least Squares (OLS) method, where explanatory variables were taken from the public and corporate finance (leverage and its determinants). Results show that long-term debt of municipalities is positively associated with the leverage and size of municipal companies, but it is negatively related to their profitability.
Keywords: G30; G32; C51; 330; debt; municipal companies; municipalities; corporate governance; off-balance-sheet financing